Social Entrepreneurship | UC Berkeley (UC Berkeley Sutardja Center, 2022)
What is Social Entrepreneurship? Social Entrepreneurship is an entrepreneurial venture with a strong community-oriented mission: examples include micro-financing or technologies for clean water in rural areas. The field has grown very quickly over the past few years, and has merged with the technology sector incredibly, with most social ventures considered unpractical if they do not…
**Carte d'information** **Type d’organisme :** Centre universitaire d'entrepreunariat et de technologie **Échelle géographique : États-Unis** **Type de contenu et outils proposés** - SkyDeck, Fung Institute, programme Engineering Leadership Professional, Global Venture Lab (partenaire Silicon Valley) - X-Lab (centre de Berkeley pour une intelligence Responsable et Décentralisée, Blockchain xcelerator, Laboratoire Date-X, Laboratoire des catastrophes, Innovation-X Lab) - Innovation-X Lab : tables rondes de l'industrie = mini-comités consultatifs, réseau et programme axés sur l'innovation - Collaborations, partenariat mondial, programme startup semester - Cours de développement professionnel, ateliers personnalisés **Public visé:** groupes universitaires, étudiant.e.s, entreprises